Pengaruh Model Problem Based Learning Berbasis TPACK Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Keanekaragaman Hayati Di SMAN 3 Pandeglang - Khotimah, Nurul; Lestari, Iing Dwi; rachmawati, Dian; Amelia, Evi (Perspektif Pendidikan dan Keguruan, 2025)
This research aims to determine the effect of the TPACK-based problem based learning model on students' critical thinking skills in biodiversity material at SMAN 3 Pandeglang. This research is experimental research using a nonequivalent control group design. The population in the study were all class X students of SMAN 3 Pandeglang for the 2024/2025 academic year. The research sample consisted of two classes, namely class X I as the control class and class X J as the experimental class. The sampling technique was carried out using simple random sampling. Data collection techniques use tests, observation sheets and documentation. The pretest-posttest results of students in the experimental class obtained an N-Gain score of 0.4 in the "medium" criteria and a class N-Gain score of 0.3 in the "low" criteria. Hypothesis testing uses the Mann-Withney U test with the Asymp.Sig value. (2-tailed) 0.000<0.005 which means H1 is accepted. Based on the hypothesis test, it can be concluded that there is an influence of the TPACK-based problem based learning model on students' critical thinking skills in biodiversity material at SMAN 3 Pandeglang.